The exchange rate insulation puzzle - Giancarlo Corsetti; Keith Küster; Gernot J. Müller; Sebastian Schmidt (European Central Bank (ECB), 2021)
We confront the notion that flexible rates insulate a country from external disturbances with new evidence on spillovers from euro-area shocks to neighboring countries. We find that in response to euro-area shocks, spillovers are not smaller, and currency movements not significantly larger, in countries that float their currency, relative to those that peg to the euro - the insulation puzzle. Unconditionally, however, currency volatility is significantly higher for floaters. A state-of-the-art open-economy model can fit our conditional evidence on lack of insulation, provided monetary policy targets headline inflation, but only at the cost of missing the unconditional evidence on currency volatility.
Keywords: F41; F42; E31; 330; Exchange-rate regime; Insulation; External shock; International spillovers; Exchange-rate disconnect